Proteomic differences among patients with heart failure taking furosemide or torsemide. Issue 3 (11th January 2022) - Cooper, Lauren B.; Bruce, Scott; Psotka, Mitchell; Mentz, Robert; Bell, Rachel; Seliger, Stephen L.; O'Connor, Christopher; deFilippi, Christopher
Abstract: Background: Loop diuretics are commonly used for patients with heart failure (HF) but it remains unknown if one loop diuretic is clinically superior. Hypothesis: Biomarkers and proteomics provide insight to how different loop diuretics may differentially affect outcomes. Methods: Blood and urine were collected from outpatients with HF who were taking torsemide or furosemide for >30 days. Differences were assessed in cardiac, renal, and inflammatory biomarkers and soluble protein panels using the Olink Cardiovascular III and inflammation panels. Results: Of 78 subjects, 55 (71%) were treated with furosemide and 23 (29%) with torsemide, and 25 provided a urine sample (15 treated with furosemide, 10 with torsemide). Patients taking torsemide were older (68 vs 64 years) with a lower mean eGFR (46 vs 54 ml/min/1.73 m 2 ), a higher proportion were women (39% vs 24%) and Black (43% vs 27%). In plasma, levels of hs‐cTnT, NT‐proBNP, and hsCRP were not significantly different between groups. In urine, there were significant differences in urinary albumin, β‐2M, and NGAL, with higher levels in the torsemide‐treated patients. Of 184 proteins testing in Olink panels, in plasma, 156 (85%) were higher in patients taking torsemide but none were significantly different after correcting for false discovery. Conclusions: We show differences in urinary biomarkers but few differences in plasma biomarkers among HF patients on different loop diuretics. Olink technology can detect differences in plasma protein levels from multiple biologic domains. These findings raise the importance of defining differences in mechanisms of action of each diuretic in an appropriately powered study.